Conservation status of amniotes found in and around Balapur Pond of District Prayagraj (Uttar Pradesh), India - Kumar Verma, Ashok (International Journal of Biological Research, 2020)
Perennial Balapur Pond was surveyed and studied to assess the conservation status of reptiles, birds and mammals naturally occurring in and around it. The survey was conducted from January 2018 to June 2019. During entire survey, a total of 7 species of reptiles, 11 species of birds and 8 species of mammals were identified. Among reptilian species reported, 1 species comes under NT (near threatened), 1 species LC (least concern) while 5 species have no special status (NSS). One avian species was CR (critically endangered), one NT (near threatened) and 9 bird species were LC (least concern). Out of 8 mammalian species recorded, one was EN (endangered), one VU (vulnerable) and remaining 6 LC (least concern).Most of the avian and mammalian species are lacking conducive ambience and hunted for food.Â Â Â